TELAAH PERTIMBANGAN HAKIM MENGABULKAN KASASI PT PLATINUM CERAMICS INDUSTRY DALAM SENGKETA PHI (STUDI PUTUSAN NO. 856 K/PDT.SUS-PHI/2020) - Habiba Nada Rezqi; Itok Dwi Kurniawan (Sebelas Maret University, 2025)
This article analyzes the judge's considerations in granting the cassation appeal of PT Platinum Ceramics Industry in the PHI dispute in Verdict No. 856 K/PDT.SUS-PHI/2020. This article is prescriptive normative legal research. The approach used in this article is a case approach. The technique of collecting legal materials used is literature study with a deductive syllogism analysis technique. The discussion of this article is the basis of the judge's considerations in granting the cassation appeal of PT Platinum Ceramics Industry. The research results show that the judge found errors in the application of the law by the judex facti, especially in evaluating the relevant evidence, and stated that the reasons submitted by Rifa'i dkk were merely differences of opinion regarding the factual assessment by the judex facti. Therefore, the judge decided to reject the appeal of Rifa'i dkk, and grant the cassation appeal of PT Platinum Ceramics Industry, annul the decision of the judex facti, and adjudicate the case independently.